Field Experiments and Numerical Analysis of the Ground Vibration Isolation of Shock Wave Propagation under Explosion Shock Loading - Wang, Iau-Teh (Vibration, 2019)
Because blast effects can jeopardize the safety of facilities, controlling blast hazards is critical in engineering design and construction. The attenuation and amplification effects generated by blast waves are affected by the topography and terrain of the blast area. This study examined the effects of topography on the propagation of seismic waves induced by explosions. From the perspective of explosion control, this study adopted explosion mechanics theories and conducted in situ explosion tests to verify finite element numerical simulation results. This study employed the finite element analysis program, to construct a 3D solid structural model to examine fluid–solid coupling, and the Multi-Material Arbitrary Lagrangian–Eulerian algorithm was adopted to develop a dynamic numerical analysis model. By analyzing the propagation of blast waves and ground vibration effects, this study examined the impact of topographical differences on blast effects. The study results may provide a reference for controlling vibration hazards subject to shock waves from explosions, in order to reduce vibrations.